IMPLEMENTASI PEMBIAYAAN BTPN SYARIAH TERHADAP PERKEMBANGAN UMKM DI KRUI LAMPUNG: IMPLEMENTATION OF BTPN SYARIAH FINANCING ON THE DEVELOPMENT OF UMKM IN KRUI LAMPUNG - Henda Alpajar; Warsiyah; Noorikha Pandayahesti Saputeri; Eki Tiyas Nurulia (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the Indonesian economy, especially in the Krui Lampung area. However, MSMEs often face capital constraints that hinder their development. BTPN Syariah is present as one of the Islamic financial institutions that focuses on financing the micro segment. This study aims to analyze the implementation of BTPN Syariah financing, measure its impact on the development of MSMEs, and identify obstacles and solutions in the implementation of financing in Krui Lampung. This study uses a descriptive qualitative method with data collection techniques through in-depth interviews, observations, and documentation. Research informant 3 officials of BTPN Syariah Krui. The data was analyzed using data reduction techniques, data presentation, and conclusion drawn. The results of the study show that the implementation of BTPN Syariah financing in Krui Lampung uses murabahah and wakalah contracts with a group system. This financing program has contributed positively to the development of MSMEs, marked by an increase in average business capital of 45%, turnover growth of 35%, and business expansion in 60% of financing customers. The main obstacles faced include limited service coverage, low understanding of sharia products, and the risk of default due to fluctuations in MSME income. The study concluded that BTPN Syariah financing plays an effective role in supporting the development of MSMEs in Krui Lampung, although there are still several challenges in its implementation. It is necessary to increase Islamic financial literacy, expand the range of services, and strengthen business assistance to optimize the impact of financing on the progress of MSMEs in the region